2013
DOI: 10.1136/bcr-2013-201436
|View full text |Cite|
|
Sign up to set email alerts
|

Small bowel injury after suprapubic catheter insertion presenting 3 years after initial insertion

Abstract: A 77-year-old woman was referred to urology with blockages of her suprapubic catheter (SPC). The catheter was replaced easily in the emergency department, however, no urine was draining, only a cloudy green fluid was visible. On cystoscopy bilious material was identified in the bladder. There was no catheter visible. There seemed to be a fistulous tract entering the bladder at the left dome. The urethra was dilated, a urethral catheter was placed and the SPC was removed. A CT demonstrated that the SPC tract tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, there have been several reports of delayed presentation of bowel perforations. Some of these have occurred following the first change of the catheter,1 4 5 others have presented up to 3 years later 6. It may be that the perforation is sealed by the catheter itself and the ensuing inflammatory fibrosis that occurs following insertion.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several reports of delayed presentation of bowel perforations. Some of these have occurred following the first change of the catheter,1 4 5 others have presented up to 3 years later 6. It may be that the perforation is sealed by the catheter itself and the ensuing inflammatory fibrosis that occurs following insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Although suprapubic catheters have many advantages, there are also several important risks and limitations to note. The most common are risk of visceral injury (bowel perforation),6,15 bleeding, hematuria, and UTI 12,16. Sheriff et al reviewed 185 cases and identified 2.7% incidence of bowel perforation, with one fatal outcome,17 but the National Patient Safety Agency placed the figure at 0.15% 18.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In a related case of obstruction, a suprapubic catheter was noted to transfix a loop of pelvic small bowel before entering the bladder. 2 Other more common complications of suprapubic catheter placement are hematuria and urinary tract infections. 3 Bowel perforation is an infrequent occurrence and is more likely to happen during routine changes of suprapubic catheters.…”
Section: Discussionmentioning
confidence: 99%